Reactive paper spray mass spectrometry for in situ identification of quinones. (15th January 2015) - Zhou, Xuan; Pei, Jiying; Huang, Guangming
<x xml:space="preserve">Abstract</x> RATIONALE The polycyclic aromatic hydrocarbons quinones are reported to be harmful and could cause mutations and cancer via the generation of reactive oxygen species through their redox cycle in human body. For detection by gas chromatography and high‐performance liquid chromatography mass spectrometry (MS), sample pretreatments and chromatographic separation prior to MS are generally required, which makes the whole analytical process laborious and time‐consuming, resulting in difficulties for fast screening targets from complicated matrices. Thus facile, rapid and reliable MS methods for detection of quinones in complicated matrices are in great demand. METHODS Reactive paper spray mass spectrometry is reported for rapid identification and quantification of quinones in complicated matrices. The method is based on an in situ derivatization reaction between cysteamine and quinones prior to analysis with paper spray mass spectrometry. With the addition of an easily charged chemical tag, the ionization efficiency of analysts is greatly improved. Due to the high ionization efficiency of the drivatives, quinones in complicated matrices could be detected rapidly without any pretreatment. RESULTS Under the optimized experimental conditions, the linear dynamic ranges for both 1, 4‐benzoquinone and 1, 4‐naphthoquinone are 0.4–40 ng and that for 1, 4‐anthraquinone is 0.4–20 ng. Limits of detection for these three analytes were measured to be 160, 40 and 200 pg using methyl‐p‐benzoquinone as internal standard. The capability to conduct MS analysis under ambient pressure is illustrated by identification of 1, 4‐naphthoquinone and 1, 4‐anthraquinone in raw urine, raw serum and cell culture medium. CONCLUSIONS Reactive paper spray could be applied to fast screening of quinones from complicated matrices. Therefore, we believe that reactive paper spray mass spectrometry might be potentially useful in the fields of environmental sciences, metabolomics and clinic analysis. Copyright © 2014 John Wiley & Sons, Ltd.